Radiological Study of Union of Lower End of Humerus and Femur for Estimation of 16 and 18 Years Age in Agra Region - Singh, Anju; Singh, Dinesh Kumar; Ahmad, Mohammad Shamim; Patil, Prakash V; Paricharak , D G (Journal of Indian Academy of Forensic Medicine, 2016)
The bony age is determined from the study of growing ends of long bones i.e. the appearance  and fusion of epiphysis with the diaphysis. The bony age is considered nearest to accuracy in estimating  the clinical age. The actual bony age can’t be determined in living, therefore the law enforcing agencies  has to rely upon radiological estimation of bony age that too with many limitations and conditions. The  present series of work was conducted at Forensic Medicine and Radiology Department of Sarojini Naidu  Medical College, Agra. The study was based on 200 cases of males and females 10-20 years of different  school and colleges running in the Agra city. In male all epiphysis of lower end of humerus are fused  except medial epicondyle at age of 16 years. Lower end of femur not fused in both males and females at  age of 16 years. In both males and females lower end of femur fused at age of 16 years.
Keywords: Skeletal age; Radiological examination; union; Femur; Humerus